Autologous transplant in multiple myeloma with an augmented conditioning protocol. Issue 11 (November 2013) - Abu Zaid, Badran; Abdul-Hai, Ali; Grotto, Itamar; Dray, Lillian; Resnick, Igor B.; Tsirigotis, Panagiotis D.; Samuel, Simcha; Or, Reuven; Shapira, Michael Y.
Abstract We compared the tolerability and anti-myeloma effect of two conditioning regimens for autologous stem cell transplant (auto-SCT) in consecutive groups of patients. Protocol 1 was the earlier, and consisted of the combination of three agents in a sequential manner, including etoposide, thiotepa and melphalan (n = 29), while protocol 2 employed melphalan alone (n = 34). The two groups were comparable (other than younger age in protocol 1). Conditioning with protocol 1 seemed more toxic, as expressed by the higher number of febrile days and higher demand for parenteral nutrition. This was not expressed with longer admission time. With 108 and 60 months' median follow-up, respectively, the median survival in patients treated by protocol 2 (melphalan 200 mg/m2) was reached at 59 months, while the median survival was not yet reached in patients treated with protocol 1 (p = 0.039). The time to progression was significantly longer with protocol 1 (median 44 months vs. 17 months with protocol 2, p = 0.033). Confounded by the small number of patients, conditioning with melphalan augmented by etoposide and thiotepa in a sequential manner is slightly more toxic than melphalan alone and may benefit patients with myeloma undergoing auto-SCT.